Analytical assays to evaluate enzymatic activity and screening of inhibitors for ornithine decarboxylase - Tinoco, Luzineide W.; da Silva Santos, Bruno Maia; Soares, Jhones Matheus da Silva; Finelli, Fernanda Gadini (Frontiers in Analytical Science, 2022)
Ornithine decarboxylase (ODC) catalyzes the decarboxylation of ornithine to produce putrescine, the first step in the metabolism of polyamines (putrescine, spermidine, and spermine), which are essential growth factors in eukaryotic cells. ODC is active as a homodimer and depends on pyridoxal 5’-phosphate (PLP) as a cofactor. An increase in the concentration of polyamines has been associated with carcinogenesis. Therefore, there is much interest in identifying inhibitors of this pathway as potential chemotherapeutic and chemopreventive agents. The best-known inhibitor of mammalian ODC is α-difluoromethylornithine (DFMO), a highly selective compound that alkylates Cys-360 (a residue of the ODC active site). Although DFMO was initially developed for the treatment of cancer, the World Health Organization recommends its use in combination with nifurtimox for the treatment of human African trypanosomiasis. Considering the importance of ODC as a promising target for the treatment of various types of cancer and other infectious diseases, choosing the right method for screening potential inhibitors can help to accelerate the discovery of new drugs. Several methods for the determination of ODC activity are found in the literature. Among these, we can mention analysis with radioactive markers, colorimetric assays using auxiliary enzymes to detect CO2 or H2O2 release, chromatographic separations with putrescine derivatization, mass spectrometry, and spectroscopic techniques. In this review, the main analysis methods used will be described, highlighting their advantages and disadvantages, as well as identifying the most promising methods for high-throughput screening.